2011
DOI: 10.1007/s00412-011-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

The template choice decision in meiosis: is the sister important?

Abstract: Recombination between homologous chromosomes is crucial to ensure their proper segregation during meiosis. This is achieved by regulating the choice of recombination template. In mitotic cells, double-strand break repair with the sister chromatid appears to be preferred, whereas interhomolog recombination is favoured during meiosis. However, in the last year, several studies in yeast have shown the importance of the meiotic recombination between sister chromatids. Although this thinking seems to be new, eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…It is known that there are several fold more double-strand breaks generated at the start of meiosis, than are processed later into COs, and that there is a significant level of double-strand break repair using sister chromatids during meiosis14. In fact it has been reported that about a third of all double-strand breaks might be repaired using sister chromatids during meiosis15.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that there are several fold more double-strand breaks generated at the start of meiosis, than are processed later into COs, and that there is a significant level of double-strand break repair using sister chromatids during meiosis14. In fact it has been reported that about a third of all double-strand breaks might be repaired using sister chromatids during meiosis15.…”
Section: Resultsmentioning
confidence: 99%
“…41) and from physical studies that identify intersister double Holiday junctions and thus presumptively intersister COs in budding yeast (42)(43)(44)(45)(46) and references therein). Also, in Arabidopsis, Mlh1 foci, which mark the sites of interfering COs (analogously to Sordaria Hei10) and colocalize with Hei10, are observed on univalents of haploid meiosis and in a dmc1 mutant, which repairs DBSs almost exclusively on sister chromatids (37).…”
Section: Recombination Between Sisters Instead Of Homologs In Karyogamy-mentioning
confidence: 99%
“…One possibility is that each site represents an SC-associated crossover, but so little SC formed at the site that forces exerted on the chromosomes during spreading pulled the two LEs apart. Alternatively, these foci may mark sites where MLH1 failed to produce crossovers, where intersister rather than inter-homolog crossovers occurred, or where interlocks had been (or were in the process of being) resolved (Schwacha and Kleckner 1994;Schwacha and Kleckner 1995;Kim et al 2010;Pradillo and Santos 2011;Storlazzi et al 2010). Whether MLH1 proteins would be present at such alternative sites in sufficient quantity to form visible foci is not known.…”
Section: Synapsis Is Homologous But Delayed and Incomplete In As1mentioning
confidence: 89%